Generalized Born-Infeld–like models for kinks and branes. (5th June 2017) - Bazeia, D.; Marques, M. A.; Menezes, R.
Abstract: In this work we deal with a non-canonical scalar field in the two-dimensional spacetime. We search for a generalized model that is twin of the standard model, supporting the same defect structure with the same energy density. We also study the stability of the defect solution under small fluctuations, which is governed by a Sturm-Liouville equation, and show how to make it stable. The model is then modified and used in the five-dimensional spacetime to construct a thick brane that engenders the first-order framework and preserves the twinlike behavior, under tensorial fluctuations of the metric in its gravitational sector.